Exploring the use of parametric design in the AEC sector to improve and ensure quality of drawings - Söderlund, Johanna; Weber, Oliwer; Ericson, Patrick; Moscati, Annika (Journal of information technology in construction, 2024)
As the Architecture, Engineering, and Construction (AEC) sector progressively embraces digital technologies, there is an emergent necessity to explore the capabilities of these tools in enhancing quality assurance and review processes during the design phase. Therefore, this study seeks to answer the following two research questions: RQ1: What types of errors can be effectively addressed using a parametric tool? RQ2: How can parametric tools be employed to ensure quality in architectural drawing and what are the potential benefits and limitations of this approach? The research employs the Design Science Research Methodology, which includes identifying issues related to drawing reviews through interviews with five industry professionals and the development of a parametric design script for drawing checking. The findings of this research have led to the development of two scripts that serve as model artifacts at a proof-of-concept level demonstrating the possibility to employ parametric design for drawing reviews. Further research could be conducted to investigate other possible applications of parametric design and automatized procedures in the AEC sector.